Kinetic and Thermodynamic Studies on the Phosphate Adsorption Removal by Dolomite Mineral - Xiaoli Yuan; Wentang Xia; Juan An; Jianguo Yin; Xuejiao Zhou; Wenqiang Yang (Journal of Chemistry, 2015)
The efficiency of dolomite to remove phosphate from aqueous solutions was investigated. The experimental results showed that the removal of phosphate by dolomite was rapid (the removal rate over 95% in 60 min) when the initial phosphate concentration is at the range of 10–50 mg/L. Several kinetic models including intraparticle diffusion model, pseudo-first-order model, Elovich model, and pseudo-second-order model were employed to evaluate the kinetics data of phosphate adsorption onto dolomite and pseudo-second-order model was recommended to describe the adsorption kinetics characteristics. Further analysis of the adsorption kinetics indicated that the phosphate removal process was mainly controlled by chemical bonding or chemisorption. Moreover, both Freundlich and Langmuir adsorption isotherms were used to evaluate the experimental data. The results indicated that Langmuir isotherm was more suitable to describe the adsorption characteristics of dolomite. Maximum adsorption capacity of phosphate by dolomite was found to be 4.76 mg phosphorous/g dolomite. Thermodynamic studies showed that phosphate adsorption was exothermic. The study implies that dolomite is an excellent low cost material for phosphate removal in wastewater treatment process.